Vehicle Engine Technologies - Cortez, Salvatore, author 644547 (Delhi, India : Research World, 2012)
A motorcycle engine drives the rear wheel of a motorcycle and powers forward motion. Motorcycle engines vary in cylinder quantity, head design, displacement and layout. Some motorcycle manufacturers have become strongly associated with one particular engine configuration. Modern Harley-Davidson motorcycles are exclusively transverse, narrow-angled V-twin engines, while Ducati and Moto Guzzi have specialised in 90° Vtwins, the former transverse and the latter longitudinal with shaft drive. Longitudinal boxer twins are iconic of BMW motorcycles, although they now use a number of different engine layouts. British marques of the 1950s and 1960s were associated with parallel-twins even though they made other types as well. Japanese manufacturers vary greatly in layouts, and Honda in particular have produced almost every possible configuration and type.